Inclusive education in the context of the conception education for all - Chavdarova-Kostova, Siyka (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
The relation between conceptions “Education for all” and “Inclusive education” is presented in the context of the their recent development. Aspects of the European and Word educational policy are commented. The development of the conception for Inclusive education is presented with some specifics regarding groups as children on the move, children under the custody of the state that were not enough discussed till now. Accent is put of the conception “learning for all "that develops the idea “education for all”.